DIỄN BIẾN VÙNG VEN BIỂN CỬA THUẬN AN (THỪA THIÊN-HUẾ) TRƯỚC VÀ SAU TRẬN LŨ LỊCH SỬ THÁNG 11-1999 - Sơn, Phạm Quang; Quân, Nguyễn Công; Đoan, Đặng Đình (Vietnam Journal of Earth Sciences, 2012)
Coastal changes in the Thuan An inlet (Thua Thien-Hue) before and after the extremely flood in November, 1999 by analysing multi - temporal remote sensing and GIS dataIn the last 45 years, the coastal area around the Thuan An inlet have been developing complicatedly by natural factors and economic-technical activities. By analysing changes in coastal areas around the Thuan An inlet, it shows that beside the normal changes are created in short time by river - sea dynamic factors, exploration and artificial modification factors but also the sudden and unusual changes are created by extraordinary weather. This was a case of extremelyraining-flooding in the beginning of November 1999 in coastal areas of the Central Vietnam, where Thua Thien - Hue province was a focus location.By studying multi-temporal remote sensing data, fieldwork and other relating document, the paper presents some newresearched results about the changes in area of the Thuan An inlet before and after the extremely flood in November, 1999 for the new assessment the potential and changes of coastal landform in context of global climate change and sea level rising.Understanding the natural affects, the human being could learn the lessons in prevention, mitigation of natural disaster and exploration of new positive aspects provided by natural changes.